Diagnosis dan Tatalaksana Juvenile Idiopathic Arthritis - Ni Luh Putu Pranena Sastri (PT. Kalbe Farma Tbk., 2021)
Juvenile Idiopathic Arthritis (JIA) merupakan kondisi inflamasi kronik pada anak, terjadi pada usia < 16 tahun pada setidaknya 1 sendi selama kurang lebih 6 bulan tanpa penyebab lain. Insiden JIA 1-22 per 100.000 dan prevalensi 7-150 per 100.000. Diagnosis JIA cukup sulit karena tidak ada pemeriksaan penunjang spesifik. Berdasarkan The International League of Associations for Rheumatology (ILAR), ada 7 jenis JIA. Tatalaksana JIA menggunakan 2011 American College of Rheumatology (ACR) Recommendations, dengan rekomendasi tahun 2019 untuk klasifikasi non-systemic polyarthritis, sacroilitis dan enthesitis.Juvenile Idiopathic Arthritis (JIA) is a chronic inflammatory condition in children, specific at <16 years of age in at least 1 joint for approximately 6 months without any other cause of joint inflammation. The incidence is 1-22 per 100,000 and prevalence is 7-150 per 100,000. Diagnosis is quite difficult because of no specific investigation and the clinical manifestations and symptoms are similar to various other diseases. Based on The International League of Associations for Rheumatology (ILAR), JIA is categorized into 7 types. Management use the 2011 American College of Rheumatology (ACR) Recommendations, with new 2019 recommendation for non-systemic polyarthritis, sacroilitis and enthesitis.